Epidemiology of Zoonotic Gastrointestinal Helminths in Stray and Pet Dogs of Dhangadhi, Nepal - Bhatta, Laxman; Pokhrel, Shekhar; Khatri-Chhetri, Rupak (Journal of Agriculture and Forestry University, 2026)
Dogs act as reservoirs of zoonotic gastrointestinal helminths, posing a significant public health risk. A cross-sectional study was conducted in Dhangadhi City, where fecal samples from 400 dogs (200 pet, 200 stray) were examined for gastrointestinal helminths. Of all samples, 173 (43.25%) fecal samples showed the presence of at least one parasite. Stray dogs showed a significantly higher prevalence (p<0.001) of helminths (63.5%) than pets (23%). The zoonotic helminths identified included: Ancylostoma spp. (19.25%), Toxocara spp. (18.50%), Taenia spp. (5.75%), and Dipylidium spp. (9.75%). The helminth prevalence was slightly higher (p>0.05) in pet dogs under 1 year (25%) compared to those over 1 year (22.4%). Single helminth infection was statistically significantly (p<0.05) higher (77.45%) than concurrent mixed infection (22.54%). Helminth prevalence was slightly higher (p>0.05) in male dogs than in females. The prevalence of zoonotic helminths was statistically significantly greater (p<0.05) in nondewormed dogs (73.9%) than in dewormed dogs (16.4%). Helminth infection was strongly associated with deworming history. The KAP survey response suggests most dog owners (88.5%) are aware of the zoonotic risk associated with dogs, and deworm their dogs within 3-6 months. Significant associations were found between gastrointestinal helminth infection and both playing behavior (p<0.05) and deworming practice (p<0.001). However, no statistically significant association was observed between the presence of helminth infection and zoonotic awareness, rearing system, and veterinary consultation practices. Responsible ownership and routine deworming practices should be followed to minimize the public health risk associated with zoonotic helminths of dogs.